Building integrated solar concentrating systems: A review. (15th February 2020) - Li, Guiqiang; Xuan, Qingdong; Akram, M.W.; Golizadeh Akhlaghi, Yousef; Liu, Haowen; Shittu, Samson
Highlights: It summarizes the building integrated solar concentrating systems according to different functions. It introduces the demands, types, applications and structures of the building integrated solar concentrating systems. It presents prospects/directions/policies around the world towards the building integrated solar concentrating systems. Abstract: In the building sector, concerns towards the vast energy consumption has promoted the development of renewable energy technologies. In this regards, the solar concentration devices show a promising concept for building applications. However, the solar concentrators for application in buildings have many restrictions, which are different from the traditional solar concentrators. The main objective of this paper is to present a concise review on the building integrated concentrating devices, that have their own characteristics and multiple functions. This paper made a classification based on device's functions, i.e. building integrated concentrated photovoltaic systems (BICPV), building integrated concentrating solar thermal (BICST) and building integrated concentrating solar daylighting (BICSD) and the combination of functions, i.e. BICPV/T, BICPV/D, BICST/D and BICPV/T/D. At the same time, this paper presented an elaborate introduction of the demands, types and applications of the building integrated concentrating devices and prospects/ directions/ policies about these technologies around the world. The review would provide important information for the actual engineering of building integrated concentrating devices.